Pengaruh Oksigen Hiperbarik Terhadap Penyembuhan Luka Jaringan (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2009)
Background: The failure of wound healing is one of the main causes of death in the sur-gery because the result is not adequate tissue oxygenation and blood perfu-sion. Patients with ischemic tissue injury, such as burns or wounds caused by traumatic and post surgery if given hyperbaric oxygen therapy may accelerate the healing process, so that the physiotherapy exercise programs for these patients would be optimized. Objective: The purpose of this study was to detect influence of hyperbaric oxygen of the acceleration of wound healing tissue. Method: Research conducted at the Naval Health Institute-Surabaya. Subject is 20 white rat with the criteria is healthy, aged 8 to 12 weeks with weight 25 to 30 grams. Analysis of data with non-parametric tests, different tests in one group pre and post the Wilcoxon test. While for different test with non-OHB group with OHB group in post test used mann-whitney test. Results: Significant diffe-rences between groups of non-OHB with OHB which significantly accelerates wound hea-ling much better than the non-OHB. Conclusion: Treatment with OHB can accelerate wound healing.Keywords: Hyperbaric Oxygen, Tissue Injury, Treatment